Modified Thomas splint‐cast combination for the management of limb fractures in small equids. Issue 3 (1st February 2017) - Ladefoged, Søren; Grulke, Sigrid; Busoni, Valeria; Serteyn, Didier; Salciccia, Alexandra; Verwilghen, Denis
Abstract: Objective: To describe the management and outcome of limb fractures in small domestic equids treated with a modified Thomas splint‐cast combination (MTSCC). Study Design: Retrospective case series. Animals: Client owned horses and donkeys. Methods: Medical records, including radiographs, were reviewed for details of animals diagnosed with a limb fracture and treated by external coaptation using a MTSCC (2001‐2012). Follow‐up >6 months after discharge was obtained via telephone consultation with owners or veterinarians. Results: Nine horses and 4 donkeys were identified with fractures of the tibial diaphysis (n = 4), ulna (n = 3), distal metatarsus (n = 2), proximal metacarpus (n = 1), radial diaphysis (n = 1), calcaneus (n = 1), and distal femoral physis (n = 1). Follow‐up was available for 12 equids, of which 8 (67%) recovered from the fracture and became pasture sound. Six equids developed obvious external deformation of the affected limb. Conclusion: Selected small equids with long bone fractures, and without athletic expectations, can be managed with external coaptation using an MTSCC. The owner should be informed that the treatment is considered a salvage procedure.